2012
DOI: 10.1039/c2dt11751g
|View full text |Cite
|
Sign up to set email alerts
|

Molybdenum(vi) catalysts obtained from η3-allyl dicarbonyl precursors: Synthesis, characterization and catalytic performance in cyclooctene epoxidation

Abstract: The oxidative decarbonylation of the η(3)-allyl dicarbonyl complexes [Mo(η(3)-C(3)H(5))Cl(CO)(2)(L)] (L = 2,2'-bipyridine (bipy) (1), 4,4'-di-tert-butyl-2,2'-bipyridine (di-tBu-bipy) (2)) by reaction with aqueous tert-butylhydroperoxide (TBHP) or H(2)O(2) gave the following compounds in good to excellent yields: the oxo-bridged dimers [MoO(2)Cl(L)](2)O (L = bipy (3), di-tBu-bipy (6)) using TBHP(10 equiv.)/CH(3)CN/r.t.; the molybdenum oxide/bipyridine hybrid material {[MoO(3)(bipy)][MoO(3)(H(2)O)]}(n) (4) and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
36
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 48 publications
5
36
0
Order By: Relevance
“…Oxoperoxo-molybdenum(VI) complexes are known to contain MoO(O 2 ) 2 , MoO(O 2 ) and MoO 2 (O 2 ) fragments, although the latter is rare [5]. These motifs are present in mononuclear complexes such as [MoO(O 2 ) 2 (L) n ] [6][7][8][9][10][11][12][13][14][15], [MoO(O 2 )Cl 2 (L) n ] acyclic alkenes. A limited number of studies have focussed on the epoxidation of olefins obtained from renewable resources such as citrus and turpentine oils, plant oils and fats [12,13,[24][25][26].…”
Section: Introductionmentioning
confidence: 97%
“…Oxoperoxo-molybdenum(VI) complexes are known to contain MoO(O 2 ) 2 , MoO(O 2 ) and MoO 2 (O 2 ) fragments, although the latter is rare [5]. These motifs are present in mononuclear complexes such as [MoO(O 2 ) 2 (L) n ] [6][7][8][9][10][11][12][13][14][15], [MoO(O 2 )Cl 2 (L) n ] acyclic alkenes. A limited number of studies have focussed on the epoxidation of olefins obtained from renewable resources such as citrus and turpentine oils, plant oils and fats [12,13,[24][25][26].…”
Section: Introductionmentioning
confidence: 97%
“…After running the catalytic process for epoxidation of cyclooctene with TBHP and various solvents, it was found that chloroform was a suitable solvent among dichloromethane, toluene, acetonitrile, chloroform, methanol and 1,2-dichloroethane with highest conversion (98%) during 10 min. By considering of mechanism in Scheme 2, it seems that the competition between methanol and acetonitrile as a coordinator solvent and (CH 3 ) 3 COO − in coordination to Mo(VI) causes a marked decrease in the catalyst activity. [37] Apparently, the lower reflux reaction temperature is the reason for the lowest epoxidation conversion in CH 2 Cl 2 (37%).…”
Section: Epoxidation Of Olefins Catalysed Bymentioning
confidence: 99%
“…[1][2][3] Molybdenum(VI) Schiff base complexes have significant advantages such as stability, economy, commercial availability and environmental friendliness in epoxidation of olefins compounds. [4][5][6][7] tert-Butyl hydroperoxide (TBHP)…”
Section: Introductionmentioning
confidence: 99%
“…A later work by another group using the 4,4'-di-tert-Bu-2,2'-bipyridine (bpy*) derivative of 4 (4a) led to the structural characterization of the products resulting from its oxidation with TBHP. [46] One of them (6c [47] in Figure 1) is very similar to our proposed species 6a and 6b. …”
Section: Chart 2 Schematic Representation Of the Isomers Of [Mo(η 3 mentioning
confidence: 62%